Hot topics in agricultural and environmental economics - a large-scale bibliometric analysis - Nils Droste; Bartosz Bartkowski; Robert Finger (Lund University, School of Economics and Management, Lund Institute for Sustainability Impact, 2021)
Land use is at the core of today's complex sustainability challenges. Agricultural and environmental economics share a focus land and resource use but evolved in their own domains. Their specialized competencies can be complementary and thus strengthen policy analysis. We use structural topic modelling on more than 24,000 articles in the top agricultural economics and environmental economics journals to derive trending topics in both fields. We thereby identify areas where the two fields converge on hot topics. We review content and contributions from each field. Our results show that policy-oriented research on land use and agent behaviour regarding multifunctional landscapes, climate change mitigation, and biodiversity conservation are hot research avenues and thus candidates for further intensified collaboration.
Keywords: Q1; Q2; Q5; 330; Bibliometrics; Content Analysis; Structural Topic Model; Sustainable Land Use